Disease-free Jute Seed Production in West Bengal - Sarkar, S K (Indian Farming, 2017)
Jute seed yield (13.2q/ha) and yield attributes are higher in mid-August sown crop with minimum seed infection (1.7%); germination (88.2–91.50%) and seedling vigour also remain above the seed recommended standard (80%); foliar spraying of carbendazim 50WP @0.2% at pod setting or pod maturation stage resulted in least seed infection and seed discolouraton which reflected on higher seed yield (11 q/ha). Thus sowing of jute seed crop during August and foliar spraying of carbendazim 50WP @ 0.2% either at pod setting or pod maturation stage is the most effective for maximization of quality jute seed with economic viability.